Influence of loneliness burden on cardio-cerebral vascular disease among the Chinese older adult: a national cohort study - Wu, Dishan; Hu, Xing; Meng, Lingbing; Li, Jianyi; Xu, Jiapei; Zhang, Luyao; Ma, Qinan; Li, Hui; Zeng, Xuezhai; Li, Juan; Zhang, Qiuxia; Liu, Deping (Frontiers in Public Health, 2024)
Background: Adverse psychosocial factors play an important role in cardio-cerebral vascular disease (CCVD). The aim of this study was to evaluate the impact of the cumulative burden of loneliness on the risk of CCVD in the Chinese elderly.: 6181 Chinese elderly over age 62 in monitoring survey of the 4th Sample Survey of the Aged Population in Urban and Rural China (SSAPUR) were included in this study. The loneliness cumulative burden (scored by cumulative degree) was weighted by the loneliness score for two consecutive years (2017-2018) and divided into low-and high-burden group. The outcome was defined as the incidence of CCVD one year later (2018-2019). A multivariate logistic regression model was used to examine the relationship between the cumulative burden of loneliness and new onset of CCVD.Results: Among participants, 18.9% had a higher cumulative burden of loneliness, and 11.5% had a CCVD incidence within one year. After multivariate adjustment, the risk of developing CCVD in group of high cumulative burden high burden group was approximately 37% higher than that in group of low cumulative burden low burden group (OR 1.373, 95%CI 1.096-1.721; P=0.006). Similar results were obtained when calculating the burden based on cumulative time. Longitudinal change of loneliness was not significantly associated with increased risk of CCVD. A higher cumulative burden of loneliness may predict a higher risk of developing CCVD in elderly individuals aged 62-72 years, or in those with diabetes.Conclusions: Cumulative burden of loneliness can be used to assess the risk of newonset CCVD in the elderly in the short term.